Prevention And Prediction of Dental Morbidity in Chemical Industry Workers - Ibragimova F.I. (Genius Publishing Group, 2021)
The aim is to develop prevention and improve the prediction of dental diseases based on the proposed conceptual approach in chemical industry workers.
Keywords: Industrial Air; chemical industry; workers